PENGETAHUAN, SIKAP, DAN PERILAKU MAHASISWA KEDOKTERAN DAN KESEHATAN TERHADAP SKRINING GENETIK DAN PREMARITAL DI KABUPATEN BANYUMAS - Nouval Keandre; Lantip Rujito; Siti Munfiah (Medical and Health Journal, 2021)
Genetic screening is a complex procedural genetical test to understand the potential genetical risk that someone might have been possessed. Screening procedure which is conducted before a couple got married is called premarital screening. Screening behavior is influenced by many factors, including predisposition, enabling, and reinforcing factors. As a healthcare provider, medical and health students must support the personal medicine concept by increasing their knowledge, attitude, and behavior. The aim of this research is to understand the relationship between knowledge level with attitude, knowledge level with behavior, and attitude with behavior among medical and health students in genetic and premarital screening. A cross-sectional study was conducted among 379 medical and health students at their first, second, and third-year (2020, 2019, and 2018) study in Banyumas Regency, selected with proportional random sampling technique. Datas were collected using Knowledge, Attitude, and Behavior in Genetic and Premarital Screening among Medical and Health Students in Banyumas Regency Questionnaire. The hypothesis was analyzed using Fisher correlation. The p-value of the Fisher correlation analysis between knowledge and attitude (p = 0,060), knowledge and behavior (p = 1,000), and attitude and behavior (p = 1,000). Participants knowledge level are at good category (75,46%) and have positive attitude (99,47%). Most of the participants’ behavior had never done genetic or premarital screening (99,47%). There was no relationship between knowledge level and attitude, knowledge level and behavior, and also attitude and behavior (p<0,05). Keywords: Attitude, Behavior, Genetic Screening, Medical and Health Students Knowledge Level, Premarital Screening